Football, lesbianism and feminism in Brazil: subversive acts - Rial, C.; de Almeida, C. S. (Soccer & Society, 2024)
Feminist voices supporting women`s football in Brazil date back to 1924, and to journalist Cléo de Galsan. But the sport was never central to the feminist agenda in the country, and a law prohibited women from playing football from 1941 to 1979. This exclusion was internalized by many women, including feminists, who expressed little interest in the world of Brazilian football. This disinterest is paradoxical, not only because of the importance of football in the national imaginary, but also because women`s sports involve fundamental dimensions in gender relations and feminist activism. The article asks why Brazilian feminism displayed little interest in this sport and concludes that part of the response lies in the social distance between feminists and footballers and in the predominance of lesbians among the athletes, while practice of football by women could be a fundamental subversive act for gender transformation.